Popular Music on Screen and the Road to Brexit (Cinéma & Cie. Film and Media Studies Journal, 2018)
This article traces some of the political and cultural implications of the use of popular music and popular musicians in British films of the 1960s and 1970s, demonstrating different, and sometimes incompatible, facets of the British psyche in relation to identity, independence, nationalism, nostalgia, and exoticism. These divergent perspectives seem to have emerged and ruptured in the 2016 Brexit vote, but are in fact deep-rooted and central to the British circumstance. Using Adler-Nissen et al.’s concept of the performativity of Brexit, which works both as a promise of a different future and to establish a specific past, various interrelationships between culture, identity politics, stardom, and music can be determined. These are explored through three general typologies — ‘Discovering Europe’, ‘Defeating Europe’, and ‘Reappraising Home’ — in order to demonstrate that the decision to leave the EU in 2016 was not a flash in the pan, but rather a long and protracted journey reflecting conflicted notions of freedom and accountability.